Long-term changes in bloom dynamics of Southern and Central Baltic cold-water phytoplankton - Paul, Carolin; Gräwe, Ulf; Kremp, Anke (Frontiers in Marine Science, 2023)
In the Baltic Sea, cold-water adapted dinoflagellates and diatoms dominate the phytoplankton spring bloom of the Northern and Eastern Basins of the Baltic Sea. In the Central and Southern parts, where such species are less prominent, they cause occasional biomass peaks. We hypothesized that these dynamics correlate with ice cover, sea surface temperature (SST), and water transport processes, as the large Basins of the Central Baltic Sea are too deep to build-up blooms from their own seed banks. Long-term monitoring data from the past 40 and 20 years in the central and southern Baltic Sea, respectively, were analyzed here for biomass development of five cold-adapted taxa: the diatoms Pauliella taeniata, Thalassiosira baltica, Thalassiosira levanderi and Melosira spp. and the dinoflagellate Peridinella catenata. Results show that diatoms generally reached high biomass peaks in the 1980s and in shorter periods from 1995-1997, 2003- 2006, and 2010-2013 in all areas. We detected good correlations with the length of the ice cover period as well as low minimum and mean winter and spring SSTs. In contrast, biomass dynamics of the dinoflagellate P. catenata are more independent from these factors but have decreased strongly since the beginning of the 21st century. A numerical ocean model analysis confirmed the hypothesis that large blooms in the deep basins are seeded through water transport from adjacent shallow, ice-covered coastal areas such as the Gulf of Finland and the Gulf of Riga. Our results show that under ongoing climate warming, the common cold-water species may disappear from spring blooms in southern and central areas with unknown consequences for the ecosystem.